Canada-DONATE study protocol: a prospective national observational study of the medical management of deceased organ donors. Issue 9 (28th September 2017) - D'Aragon, Frederick; Dhanani, Sonny; Lamontagne, Francois; Cook, Deborah J; Burns, Karen; Akhtar, Aemal; Chassé, Michaël; Frenette, Anne-Julie; Keenan, Sean; Lize, Jean-Francois; Kutsogiannis, Demetrios J; Kramer, Andreas; et al.
Abstract : Introduction: Research on the management of deceased organ donors aims to improve the number and quality of transplants and recipient outcomes. In Canada, this research is challenged by regionalisation of donation services within provinces and the geographical, clinical and administrative separation of donation from transplantation services. This study aims to build a national platform for future clinical trials in donor management. Objectives are to engage collaborators at donation hospitals and organ donation organisations (ODOs) across Canada, describe current practices, evaluate the effectiveness of donation-specific interventions and assess the feasibility of future clinical trials. Methods and analysis: This ongoing prospective observational study of the medical management of deceased organ donors will enrol more than 650 consented potential donors from adult intensive care units at 33 hospital sites across Canada, each participating for 12 months. ODOs ensure enrolment of consecutive eligible participants. Research staff record detailed data about participants, therapies, organ assessments, death declaration procedures and adverse clinical exposures from the time of donation consent to organ recovery. ODOs provide reasons that organs are declined, dates and places of transplantation, and recipient age and sex. Descriptive analyses will summarise current practices. Effectiveness analyses will examine donation-specific interventions with respect to the number of transplants, using multilevel regression models to account for clustering by donor, hospitals and ODOs. Feasibility analyses will focus on acceptance of the research consent model; participation of academic and community hospitals as well as ODOs; and accessibility of recipient data. Ethics and dissemination: This study uses a waiver of research consent. Hospitals will receive reports on local practices benchmarked to (1) national practices and (2) national donor management guidelines. We will report findings to donation and transplant collaborators (ie, clinicians, researchers, ODOs) and publish in peer-reviewed journals. Trial registration number: NCT03114436.